LEXICO-STYLISTIC CHOICES AND MEDIA IDEOLOGY IN NEWSPAPER REPORTS ON NIGER DELTA CONFLICTS - Ononye, Chuka Fred (Universitas Pendidikan Indonesia, 2017)
Media reports on Niger Delta (Henceforth, ND) conflicts have reflected a relationship between lexico-stylistic choices and media ideologies. The existing media studies on the discourse have predominantly utilised pragmatic, stylistic and discourse analytical tools in presenting and labelling discourse participants and/or their ideologies, but neglected how media ideologies can be revealed through lexico-stylistic choices made in the reports. This paper therefore examines the lexico-stylistic choices in the reports in order to establish their link to specific ideological goals of the newspapers in relaying the conflict news. Forty reports on ND conflicts, published between 2003 and 2007, sampled from two ND-based (The Tide and Pioneer) and two national (The Punch and THISDAY, labelled) newspapers, were subjected to stylistic and critical analyses, with insights from structural (relational) semantics and aspects of stylistics discourse. Two broad lexical stylistic choices are identified, including paradigmatic (61.8%—indexed by synonymous, antonymous, hyponymous, colloquial, and register items, and coinages) and syntagmatic (38.2%—marked by collocations, metaphors, pleonasms, and lexical fields) features. The features are utilised for three ideological ends; namely, picking out and framing participants as perpetrators of the violence in the discourse, evaluating specific entities and their roles in the conflicts, and reducing the impact of the activities of the news actors. Although there are overlaps, the evaluative ideology is largely associated with the national newspaper, the impact reduction ideology with the ND-based newspapers, while the framist ideology is observed in the two sets of newspapers. With these findings the study has added the lexical stylistics angle to the existing scholarship on ND conflict news discourse. Thus, the newspaper reports on ND conflicts are motivated by their ideological goals to change the reader’s outlook on the issues relating to the conflicts.